Myocardial bridge in a child without hypertrophic cardiomyopathy: A case report - Yadav, Shiv Kumar; Zhou, Xue; He, Ling; Yi, Qi-jian (Asian Journal of Medical Sciences, 2014)
In children, myocardial bridge is an inborn coronary anomaly and is usually found in the patients with hypertrophic cardiomyopathy or left ventricular hypertrophy. Myocardial bridges were long thought to be a benign anatomical variant, even in patients with obstructive and non-obstructive hypertrophic cardiomyopathy. However some patients suffer from myocardial infarction, arrhythmia and even sudden cardiac death. In the present report, we describe a 7-year-old girl with the manifestation of recurrent precordial discomfort, and subsequently diagnosed as having an isolated myocardial bridge in the distal segment of left anterior descending coronary artery using 64-slice computed tomography coronary angiography. DOI: http://dx.doi.org/10.3126/ajms.v6i4.11785 Asian Journal of Medical Sciences Vol.6(4) 2015 80-82